2014
DOI: 10.1002/cbdv.201400190
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Nitric Oxide Production‐Inhibitory Activities of Limonoids and Other Compounds from the Leaves and Bark of Melia azedarach

Abstract: Nine limonoids, 1-9, one apocarotenoid, 11, one alkaloid, 12, and one steroid, 13, from the leaf extract; and one triterpenoid, 10, five steroids, 14-18, and two flavonoids, 19 and 20, from the bark extract of Melia azedarach L. (Chinaberry tree; Meliaceae) were isolated. Among these compounds, three compounds, 4-6, were new, and their structures were established as 3-deacetyl-28-oxosalannolactone, 3-deacetyl-28-oxosalanninolide, and 3-deacetyl-17-defurano-17,28-dioxosalannin, respectively, on the basis of ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…13, 8 new limonoids, including 3-deacetyl-28-oxosalannolactone 300, 3-deacetyl-28-oxosalanninolide 301, 3-deacetyl-17-defurano-17,28-dioxosalannin 302, 3-deacetyl-4 0 -demethylsalannin 303, 3-deacetyl-28-oxosalannin 304, 1-detigloylohchinolal 305, 3a-acetoxy-1a,7a-dihydroxy-12a-methoxynimbolinin 306, and 3a-acetoxy-1a,12a-dihydroxy-7a-(2-methylprop-2-enoyl)nimbolinin 307, were isolated from the leaves, fruits and stem barks of Melia azedarach. [102][103][104] Recently, an investigation on the fruits of M. toosendan resulted in four new limonoids, such as 1a,7a-dihydroxyl-3a-acetoxyl-12a-ethoxylnimbolinin 308, 105 1a-tigloyloxy-3a-acetoxyl-7a-hydroxyl-12b-ethoxylnimbolinin 309, 105 (Fig. 14), was isolated from the bark of Chisocheton cuminganus.…”
mentioning
confidence: 99%
“…13, 8 new limonoids, including 3-deacetyl-28-oxosalannolactone 300, 3-deacetyl-28-oxosalanninolide 301, 3-deacetyl-17-defurano-17,28-dioxosalannin 302, 3-deacetyl-4 0 -demethylsalannin 303, 3-deacetyl-28-oxosalannin 304, 1-detigloylohchinolal 305, 3a-acetoxy-1a,7a-dihydroxy-12a-methoxynimbolinin 306, and 3a-acetoxy-1a,12a-dihydroxy-7a-(2-methylprop-2-enoyl)nimbolinin 307, were isolated from the leaves, fruits and stem barks of Melia azedarach. [102][103][104] Recently, an investigation on the fruits of M. toosendan resulted in four new limonoids, such as 1a,7a-dihydroxyl-3a-acetoxyl-12a-ethoxylnimbolinin 308, 105 1a-tigloyloxy-3a-acetoxyl-7a-hydroxyl-12b-ethoxylnimbolinin 309, 105 (Fig. 14), was isolated from the bark of Chisocheton cuminganus.…”
mentioning
confidence: 99%
“…siamensis , and M . azedarach , while seven are semi‐synthetic compounds derived from the Meliaceae limonoids (see for details). Two, 2 and 32 , and five, 19 , 22 , 23 , 43 , and 67 , other limonoids were isolated from the non‐saponifiable lipid (NSL) fraction of A .…”
Section: Resultsmentioning
confidence: 99%
“…var. siamensis Valeton (Siamese neem tree), and Melia azedarach L. (chinaberry tree), as well as on the semi‐synthetic limonoids derived from the Meliaceae limonoids, was undertaken, and this showed that some limonoids exhibit potent inhibitory activities against melanogenesis in B16 melanoma cells, against 12‐ O ‐tetradecanoylphorbol‐13‐acetate (TPA)‐induced inflammation in mice, and against TPA‐induced Epstein–Barr virus early antigen activation, as well as cytotoxic and apoptosis‐inducing activities against human cancer cell lines . In addition, some limonoids from M .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploration of anticancer herbal with high effectiveness and minimum side effects need to be developed. One of the plants that potentially contains anticancer compounds is Melia azedarach (Pan et al 2014). This plant is versatile because it can be used for various purposes including health remedy .…”
mentioning
confidence: 99%